THE MAIN CHARACTER DEVELOPMENT AND GOTHIC CONVENTIONS IN RUDNICK’S MALEFICENT NOVEL - Alvionita Alvionita; Anjar Dwi Astuti; Nasrullah Nasrullah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2022)
ABSTRACT This study aimed at analyzing how the character development of the main character influenced the gothic conventions in Maleficent novel. In order to get more thorough understanding, theories by Hurlock and Snodgrass were employed. For personality development, it is divided into eight determinants, there are physical determinants, intellectual determinants, emotional determinants, social determinants, aspirations and achievements, sex determinants, educational determinants, and family determinants. For gothic conventions, there are atmosphere, setting, revenge, and supernatural. In order to identify the personality development and gothic conventions, qualitative research was employed to explore further. The result showed that Maleficent as the main character experienced personality development, there are physical changes, emotional changes and family who always stand with her. For gothic conventions, Maleficent experienced all of the type there are atmosphere, revenge and supernatural.Keywords: personality develoment, gothic conventions, gothic literature, Maleficent, fairy  ABSTRAK Penelitian ini bertujuan untuk menganalisis bagaimana perkembangan karakter dari tokoh utama yang mempengaruhi kaidah-kaidah gothic dalam novel Maleficent. Untuk mendapatkan pemahaman yang lebih menyeluruh, penulis menggunakan teori Hurlock dan Snodgrass. Untuk perkembangan karakter dibedakan menjadi delapan faktor yaitu faktor fisik, faktor intelektual, faktor emosional, faktor sosial, aspirasi dan prestasi, faktor jenis kelamin, faktor pendidikan, dan faktor keluarga. Untuk kaidah gothic, diantaranya suasana, balas dendam, dan supernatural. Untuk mengindentifikasi perkembangan kepribadian dan kaidah-kaidah gothic, penelitian kualitatif digunakan untuk mengeksplorasi lebih jauh. Hasil dari penelitian menunjukkan bahwa Malefient sebagai tokoh utama mengalami perkembangan kepribadian, terjadi perubahan fisik, perubahan emosi, dan keluarga yang selalu mendampingi dirinya. Untuk kaidah gothic, Maleficent mengalami semua jenis yaitu suasana, balas dendam dan supernatural.Kata kunci: perkembangan kepribadian, kaidah-kaidah gothic, sastra gothic, Maleficent, peri